Perfil lipídico en leche de vacas en pastoreo de gramíneas en el trópico seco colombiano - Mojica Rodríguez, José Edwin; Castro Rincón, Edwin; Carulla-Fornaguera, Juan Evangelista; Lascano Aguilar, Carlos Eduardo (Universidad de Costa Rica, 2019)
The composition of fat in bovine milk has relevance in human health, where polyunsaturated fatty acids such as conjugated linoleic acid (ALC c9 t11) have positive effects (anticarcinogenic, antidiabetogenic). There are investigations regarding the effect of bovine feeding on milk quality in temperate zones (above 2200 m.a.s.l.), but few in the Colombian low tropics (below 1500 m.a.s.l.). Objetive. The objective of this work was to evaluate the effect of three grasses Mulato II, Tanzania, and Toledo on production, composition, and lipid panel in the milk of Gyr x Brown Swiss cows in the first-second-and three-third of lactation. Materials and methods. The study was conducted from May to June 2013 in the city council of San Diego, Cesar, Colombia. Two groups of nine animals were selected (three cows in each third lactation stage), and one cow was assigned to each grass in a replicated 3 x 3 Latin Square design. Results. Milk production was similar (p>0.05) in evaluated grasses and decreased (p<0.05) as the lactation advanced. The concentration of milk fat and protein was higher (p<0.05) in Tanzania and Mulato II, although in the second-third there was a higher content (p<0.05) of polyunsaturated acids, compared to Toledo. The lactation trimester did not affect (p>0.05) milk composition. There was higher fed (p<0.05) concentration of conjugated linoleic acid and polyunsaturated fatty acids in milk fat in cows fed with Tanzania and Toledo forage. Conclusion. Feeding dual-purpose cows with Tanzania and Toledo grasses could have positive effects on human health, due to the healthier lipid panel of the milk produced.